Characterization of Three Alboaggregins Purified from Trimeresurus albolabris Venom - Peng, Manling; Lu, Weiqi; Kirby, Edward P (Thrombosis and Haemostasis, 1992)
Alboaggregins (AL-A, AL-B, AL-C) isolated from Trimeresurus albolabris snake venom represent a new family of proteins which bind to platelet glycoprotein lb (GPIb). These alboaggregins were purified to homogeneity with ion exchange HPLC (Mono-Q column) and hydrophobic HPLC (TSK Phenyl-5PW column). On SDS-polyacrylamide gel electrophoresis, apparent molecular weights of AL-A, AL-B and AL-C were 52 kDa, 26 kDa, and 121 kDa respectively, under nonreducing conditions. Upon reduction, each alboaggregin showed two types of chains with apparent molecular weights in the range of 15-20 kDa. All three alboaggregins agglutinated formalin-fixed platelets. Agglutination activities and binding of labeled alboaggregins to GPIb were specifically inhibited by the monoclonal antibody AK2 which is directed against the 45 kDa N-terminal region on GPIb, but not by monoclonal antibodies against other epitopes on GPIb. 125I-alboaggregin binding to platelets was not altered by the presence of thrombin. Alboaggregins did not bind to GPIIb/IIIa. Alboaggregins were competitive inhibitors for 125I-bovine vWF binding to platelets. Mutual competition studies between AL-A, AL-B and AL-C for the binding of labeled bovine vWF and AL-B to platelets demonstrated that AL-B and AL-C had a significantly higher affinity than AL-A.